An Analysis of Junior High School Students’ Attitude in Learning English - Panjaitan, Miranda; Nasution, Jamaluddin; Srisna J. Lahay (Teaching English and Language Learning English Journal, 2025)
This study explores the attitudes of junior high school students toward learning English and the factors influencing their engagement and performance in English classrooms. Adopting a descriptive qualitative approach, the research aims to identify students’ emotional, cognitive, and behavioral dispositions toward English as a foreign language. Data were collected through questionnaires and interviews, focusing on the nature of students’ attitudes (positive or negative), the underlying factors (such as teacher influence, parental support, peer environment), and the effects of these attitudes on classroom participation. The findings reveal that while many students show interest in learning English, negative perceptions related to difficulty and anxiety persist. Factors such as teaching strategies, classroom climate, and social support significantly shape student attitudes. The study highlights the importance of fostering positive learning environments and tailored instructional approaches to enhance student motivation and academic success in English language education.